Electrochemical Fabrication of Highly Ordered ZrO2-HfO2 Binary Oxides Nanotube Arrays - Li, Lingjie; Xu, Jing; Lei, Jinglei; He, Jianxin; Zhang, Jiarui; Li, Nianbing; Zhang, Shengtao (Asian Journal of Chemistry, 2014)
The present work demonstrates a facile approach to fabricate highly ordered nanotubular ZrO2-HfO2 binary oxides. Zr-Hf alloy was electrochemically anodized in an ethylene glycol electrolyte containing small amounts of fluoride via a two-step process. The field emission scanning electron microscopy images show the highly ordered nanotube arrays with a length of approximately 6.8 μm, an average diameter of approximate 32 nm and a tube density of 3 × 1010 cm-2 were formed on the Zr-Hf alloy surface. X-ray photoelectron spectroscopy analysis provides evidence that the composition of the formed nanotubes is ZrO2-HfO2 binary oxides. X-ray diffraction studies indicates that monoclinic ZrO2 and HfO2 with small amount of tetragonal phase ZrO2 coexist in the nanotubular binary oxides layer after thermal annealing at 400 °C for 3 h. The present electrochemical approach can be extended to prepare the highly ordered nanotubular oxides with a wide range of composition and functionalities.